Beyond Class Stratification: The Rise of the Eclectic Music Consumer in the Modern Age. (September 2018) - Nuccio, Massimiliano; Guerzoni, Marco; Katz-Gerro, Tally
This article contributes to the literature on the association between class position and cultural tastes by analyzing a unique historical data set and asking whether there were significant class differences in the consumption of music in the 19th century. Archival data from a publisher in Milan are used to analyze the characteristics of customers who purchased sheet music between 1814 and 1823. To avoid contemporary depictions of cultural hierarchies (e.g. 'highbrow', 'lowbrow' and 'omnivorous' tastes), we offer a new method for considering both the quantitative and qualitative dimensions of music consumption. Considering both the aggregate level of music consumption and the evolution of individual patterns over time, we find little evidence that musical tastes were aligned with class position. This finding calls for more research on the origins of the strong link between social structure and cultural preferences in general, or between class position and musical tastes in particular, which we witness today.